2015
DOI: 10.1021/ef502518n
|View full text |Cite
|
Sign up to set email alerts
|

Poplar Liquefaction in Water/Methanol Cosolvents

Abstract: Poplar liquefaction (PL) in methanol, water or water/methanol co-solvents (WMCSs) was investigated at 240-320 o C for 0-90 min. The results show that the yields of bio-oils (BOs) obtained from PL in WMCSs are higher than those in either methanol or water, indicating that methanol has synergic effect with water on PL. The maximum BO yield of 44.2% was obtained at 270 o C for 15 min in a WMCS containing 70 vol% of water. The BOs were analyzed with a gas chromatograph/mass spectrometer (GC/MS) and Fourier tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
9
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(10 citation statements)
references
References 42 publications
0
9
1
Order By: Relevance
“…In other words, the optimal temperature should be 300°C for obtaining maximum BO yield of 40.5% from SSS liquefaction. Comparing to our previous studies [26,28], the BO yield obtained from either cornstalk or poplar liquefaction is ca. 10% less than that from SSS liquefaction.…”
Section: Liquefaction Procedures and Characterizationcontrasting
confidence: 55%
See 3 more Smart Citations
“…In other words, the optimal temperature should be 300°C for obtaining maximum BO yield of 40.5% from SSS liquefaction. Comparing to our previous studies [26,28], the BO yield obtained from either cornstalk or poplar liquefaction is ca. 10% less than that from SSS liquefaction.…”
Section: Liquefaction Procedures and Characterizationcontrasting
confidence: 55%
“…MBs (Table 5) should be originated from the depolymerization of lignin in SSS [26]. The total yield of PCs first increased but then decreased under the reaction conditions.…”
Section: Analyses Of the Bos With Ftir And Gc/msmentioning
confidence: 99%
See 2 more Smart Citations
“…It was found that a 50/50 (v/v) ratio of a methanol-water mixture provided heavy oil with the highest phenol content. In a similar study, Yan et al [134] reported that methanol is effective for the degradation of cellulose and hemicellulose, whereas better lignin degradation is found when only water is used. Water contributed to the hydrolysis of cellulose and hemicellulose components, and led to ketone formation through cyclization reactions and methanol-facilitated esterification reactions [131,134].…”
mentioning
confidence: 92%